Analisis Penerapan Akuntansi UMKM Berbasis SAK EMKM Pada Nyushiin Medan Solusi Transparansi Dan Efisiensi Keuangan - Syifa, Naila Jayida; Rahmani, Nur Ahmadi Bi; Nasution, Yenni Samri Juliati (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in the culinary business Nyushiin Medan as an effort to improve transparency and efficiency of financial management. The method used was descriptive qualitative, with data collection techniques including observation, in-depth interviews, and documentation of financial reports from 2022 to 2024. The results indicate that the implementation of SAK EMKM is still partial and unsystematic. The prepared financial reports do not fully follow the standard format, particularly in the preparation of the Statement of Financial Position and Notes to the Financial Statements (CALK). However, transparency has increased through neater recording of daily transactions and the separation of personal and business finances. The implementation of a simplified income statement also encourages efficiency, as evidenced by the business's ability to reduce promotional costs and increase product profit margins. The main obstacles to the implementation of SAK EMKM are low accounting literacy and a lack of external mentoring. Therefore, support from the government, academics, and financial institutions is essential to encourage the comprehensive implementation of SAK EMKM-based accounting in the MSME sector.